'Nausicaa' compression suture: a simple and effective alternative to hysterectomy in placenta accreta spectrum and other causes of severe postpartum haemorrhage. (20th August 2018) - Shih, J‐C; Liu, K‐L; Kang, J; Yang, J‐H; Lin, M‐W; Yu, C‐U
Abstract : Postpartum haemorrhage (PPH), especially resulting from placenta accreta spectrum (PAS), has become a worldwide concern in maternity care. We describe a novel method of uterine compression sutures (the 'Nausicaa' technique) as an alternative to hysterectomy for patients who have suffered from major PPH. We applied this technique in 68 patients with major PPH during caesarean section (including 43 patients with PAS, 20 patients with placenta praevia totalis, and five patients with uterine atony), and none of these patients required further hysterectomy. We conclude that our Nausicaa suture is a simple and feasible alternative to hysterectomy in patients suffering from major PPH.